Characterization and genome sequence of N,N-dimethylformamide degradation in Paracoccus sulfuroxidans DM175A1-1 isolated from activated sludge of wastewater - Zheng, Gang; Su, Yue; Zhang, Wenwu; Liu, Xingping; Shao, Li; Shen, Zhibo; Zhang, Dongdong; Wang, Kaiyang; Miao, Zhoudi (Frontiers in Microbiology, 2024)
N,N-dimethylformamide (DMF) is an organic solvent with stable chemical properties and high boiling point. Based on its good solubility, DMF is widely used in synthetic textile, leather, electronics, pharmaceutical and pesticide industries. However, the DMF pollutes the environment and does harm to human liver function, kidney function, and nerve function. Herein, an efficient DMF-degrading strain, DM175A1-1, was isolated and identified as Paracoccus sulfuroxidans. This strain can use DMF as the sole source of carbon and nitrogen. Whole-genome sequencing of strain DM175A1-1 revealed that it has a 3.99-Mbp chromosome a 120-kbp plasmid1 and a 40-kbp plasmid2. The chromosome specifically harbors the dmfA1 and dmfA2 essential for the initial steps of DMF degradation. And it also carries the some part of genes facilitating subsequent methylotrophic metabolism and glutathione-dependent pathway. Through further DMF tolerance degradation experiments, DM175A1-1 can tolerate DMF concentrations up to 10000 mg/L, whereas the majority of Paracoccus strains could only show degradation activity below 1000 mg/L. And the efficiency of organic nitrogen conversion to NH3-N in DMF can reach 99.0% when the hydraulic retention time (HRT) is controlled at 5 d. Meanwhile, it showed a significant degradation effect at a pharmaceutical enterprise in Zhejiang Province with high concentration of DMF wastewater. This study provides a new strain Paracoccus sulfuroxidans DM175A1-1 which shows a significant influence on DMF degradation, and reveals the characterization on its DMF degradation. It lays the foundation for the application of biological method in the efficient degradation of DMF in industrial wastewater.